Excitation of TM mode by a relativistic electron beam in an azimuthally corrugated waveguide - Ognivenko, V.V. (Problems of Atomic Science and Technology, 2023)
The excitation of an electromagnetic TM mode by a relativistic electron beam in a waveguide with a sinusoidalcorrugated azimuth conducting wall in a constant uniform external guiding magnetic field is theoretically studied. We consider a thin annular electron beam moving along the waveguide axis and rotating at an equilibrium radius around its axis. In the approximation of a small corrugation depth, the analytical dependences of the growth rate of instability and resonant frequencies on the parameters of the beam and waveguide are determined. Теоретично досліджено збудження електромагнітної ТМ-хвилі релятивістським електронним пучком у хвилеводі з синусоїдально гофрованою по азимуту провідною стінкою у постійному однорідному зовнішньому ведучому магнітному полі. Розглянуто тонкий трубчатий електронний пучок, що рухається вздовж осі хвилеводу і обертається на рівноважному радіусі навколо його осі. У наближенні малої глибини гофра визначені аналітичні залежності інкрементів нестійкості і резонансних частот від параметрів пучка і хвилеводу.